Case reportsPercutaneous retrieval of a detached rotational atherectomy burr - Kosowski, Michał; Zimoch, Wojciech; Kübler, Piotr; Wojtczak, Marcin; Telichowski, Artur; Reczuch, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Rotablation (rotational atherectomy) is an acknowledged method of percutaneous treatment of highly calcified coronary artery lesions that cannot be treated with traditional angioplasty. The complexity of the technique and usage of very specific equipment can contribute to the development of uncommon complications. We present a case of percutaneous retrieval of a damaged rotational atherectomy burr in a 74-year-old male patient.